Perfil microbiológico de úlceras infectadas em pacientes com pé diabético e associação com amputação maior e com óbito - Natália Anício Cardoso (2016)
Introduction: diabetic foot infection is one of the leading causes of lower limb amputation and death. Diabetic foot is the major cause of hospitalization and financial burden in the diabetic population and is considered a serious public health problem. Objective: identify the microbiological profile of infected ulcers in patients with diabetic foot, correlating with major amputation and death. Method: it was performed two case-control studies, in which the case-control study 1 compared patients who underwent major amputation (cases) and patients without amputation (controls). The case-control study 2 compared patients that underwent major amputation and died (cases) and patients that underwent major amputation who survived (controls). Results: the case-control study 1 consisted of 189 patients with a mean age of 61.9 years, mostly males (64.6%), with mean serum creatinine level of 1.95 mg/dL and average level of serum hemoglobin of 8.93 g/dL. The readmission rate was 42.9% and the death rate was 15.9%. Of these patients, 86.8% had positive culture, and 72.0% were monomicrobial cultures and 21.2% had reinfection. The most common genres of bacteria were Acinetobacter spp. (24,4%), Morganella spp. (24,4%), Proteus spp. (23,1%) and Enterococcus spp. (19,2%) and species were Acinetobacter baumannii, Morganella morganii, Pseudomonas aeruginosa and Proteus mirabilis. The genera Acinetobacter spp. and Klebsiella spp., level creatinine serum 1,3 mg/dL and level hemoglobin serum < 11 g/dL were predictive for major amputation. The case-control study 2 consisted of 78 patients with a mean age of 63.8 years, mostly males (69.2%), with mean serum creatinine level of 2,49 mg/dL and average level of serum hemoglobin of 7.36 g/dL. The readmission rate was 47.4% and 59.0% of the subjects had transtibial amputation and 39.7% underwent transfemoral amputation. Of these patients, 87.2% had positive culture, and 68.0% were monomicrobial cultures and 30.8% had reinfection. The most common genres of bacteria were Acinetobacter spp. (33,3%), Morganella spp. (33,3%) and Proteus spp. (27,8%) and species were Acinetobacter baumannii and Morganella morganii. No bacterial genre was predictive for death. Level creatinina serum 1.3 mg/dL and transfemoral amputation were predictive for death. Conclusion: in patients submitted to major amputation, the most common genres of bacteria were Acinetobacter spp., Morganella spp., Proteus spp. and Enterococcus spp. and species were Acinetobacter baumannii, Morganella morganii, Pseudomonas aeruginosa and Proteus mirabilis. The genres Acinetobacter spp. and Klebsiella spp., level creatinine serum 1,3 mg/dL and level hemoglobin serum < 11 g/dL were predictive for major amputation. In patients submitted to major amputation who died, the most common genres of bacteria were Acinetobacter spp., Morganella spp. and Proteus spp. and species were Acinetobacter baumannii and Morganella morganii. Level creatinina serum 1.3 mg/dL and transfemoral amputation were predictive for death. No bacterial genre was predictive for death. Polimicrobial cultures and reinfection of infected ulcers in patients with diabetic foot were not associated with major amputation and death.